The Influence of Perceived Usefulness, Ease of Use, Security, and Trust on Intention to Use DANA E-Wallet - Yohanis Rante; Indra Eka Wardana Toii (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Micro, Small, and Medium Enterprises play a crucial role in Indonesia’s economy, particularly in North Sumatra, yet struggle to access Islamic banking financing due to internal and external challenges. This study seeks to develop strategies for enhancing partnership-based financing for these enterprises within Islamic banks. Employing the Analytic Network Process, the research engaged nine key informants from academia, regulatory bodies, and Islamic banking practitioners through in-depth interviews and pairwise comparison questionnaires to prioritize solutions. Findings reveal that insufficient bank staff expertise in understanding the needs of these enterprises is the primary internal barrier, while dependence on personal or informal capital poses the main external obstacle. Key strategies include targeted staff training, fostering multi-stakeholder partnerships, promoting enterprise products digitally, and implementing policies for financing subsidies and collaboration forums. This study provides a strategic framework for inclusive, sharia-compliant financing to drive regional economic growth. Limited to North Sumatra with a small informant sample, the findings may not fully apply elsewhere. The proposed strategies offer practical guidance for banks and policymakers to strengthen financing ecosystems, promoting sustainable development for these enterprises.